Aqueous slurry for positive electrode, positive electrode composition, lithium ion secondary battery comprising the positive electrode composition and method for producing the same
By using fluoride-containing polymers and CMC aqueous cathode slurry in the cathode of lithium-ion secondary batteries, the cycle life and safety of the cathode under high temperature and high voltage conditions is solved, and high lithium ion conductivity, adhesion and chemical stability are achieved.
Patent Information
- Application Number
- CN202080086676.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-12-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-12-24
AI Technical Summary
The prior art is difficult to achieve high cycle life and safety in the positive electrode of lithium-ion secondary batteries, especially under high temperature and high voltage conditions.
Using an aqueous positive electrode slurry containing fluoride-based polymer and carboxymethylcellulose (CMC), lithium ion conductivity, adhesion and chemical stability are improved by attaching fluoride-based polymer particles to the surface of the positive electrode active material particles.
High cycle characteristics and safety under high temperature and high voltage conditions are achieved, extending the cycle life of the battery and improving the chemical stability of the battery.
Smart Images

Figure CN114830378B_ABST
Abstract
Description
Technical Field
[0001] This application claims priority to Japanese Patent Application No. 2019-236899 filed in the Japan Patent Office on December 26, 2019, the disclosure of which is incorporated herein by reference in its entirety. The present invention relates to an aqueous slurry for a positive electrode, a positive electrode composition, a lithium ion secondary battery comprising the positive electrode composition, and a method for manufacturing the same. Background Art
[0002] As the application range of lithium-ion secondary batteries as power sources continues to expand, development is sought in the pursuit of higher energy in the form of active materials with higher theoretical capacity or expanding the operating voltage range, and the battery is required to operate stably over a wide temperature range. Therefore, it is more difficult to ensure cycle life or safety. The solution is to transform the negative electrode material such as the binder used in lithium-ion secondary batteries from non-aqueous to aqueous to enhance the bonding between the electrode and the current collector, thereby improving high cycle performance.
[0003] Patent Document 1 achieves a long cycle life by using carboxymethyl cellulose (CMC) / styrene butadiene rubber (SBR) having a high binding force as an aqueous binder in a negative electrode.
[0004] On the other hand, in the positive electrode with a low volume expansion rate during charge / discharge, the resistance and chemical stability of the binder have a much greater impact on the battery characteristics than the binding force compared to the negative electrode, so the development route is very different. For example, when an aqueous binder is applied to the positive electrode, the resistance of SBR increases and oxidative degradation occurs due to the coating performance of CMC. Therefore, for the positive electrode, the binder is less converted from non-aqueous to aqueous in order to improve the cycle characteristics, and a dispersion of polyvinylidene fluoride (PVDF) and / or polytetrafluoroethylene (PTFE) in N-methyl-2-pyrrolidone (NMP) is still used.
[0005] However, there have been reports of gas generation or electrode separation due to PVDF decomposition during charge / discharge cycles at high temperatures and high voltages, and given the current trend towards high-temperature, high-voltage batteries and the research conducted so far on aqueous binders for negative electrodes, expectations for aqueous binders for positive electrodes are very high.
[0006] Patent Documents 2 and 3 propose the use of an aqueous binder in a positive electrode, but an aqueous binder having a long cycle life and high safety has not yet been achieved.
[0007] Related Literature
[0008] [Patent Document]
[0009] Patent Document 1: Japanese Patent Publication No. 2006-107896
[0010] Patent Document 2: Japanese Patent Publication No. 2015-088276
[0011] Patent Document 3: Japanese Patent Publication No. 2014-063676 Summary of the invention
[0012] Technical issues
[0013] Therefore, a first object of the present invention is to provide an aqueous slurry for a positive electrode, which includes an aqueous binder for a positive electrode having improved lithium ion conductivity, adhesion and chemical stability.
[0014] In addition, a second object of the present invention is to provide a positive electrode composition prepared from the positive electrode aqueous slurry.
[0015] In addition, a third object of the present invention is to provide a lithium ion secondary battery comprising the positive electrode composition.
[0016] Technical Solution
[0017] The first aspect of the present invention relates to an aqueous positive electrode slurry, the aqueous positive electrode slurry comprising a positive electrode active material, a water-borne binder, a water-soluble polymer and an aqueous solvent. The water-soluble polymer comprises carboxymethyl cellulose (CMC). The positive electrode active material and the water-borne binder are dispersed in the aqueous positive electrode slurry.
[0018] According to a second aspect of the present invention, the fluoride-based polymer in the first aspect is in a particle form. In addition, the fluoride-based polymer is at least one selected from the following: polyvinylidene fluoride (PVDF), PVDF-HFP, PVDF-CTFE, PVDF-TrFE, PVDF-TFE.
[0019] According to a third aspect of the present invention, the fluoride-based polymer particles in the first or second aspect may have an average particle diameter of 50 nm to 250 nm, and the aqueous solvent may be water.
[0020] On the other hand, in the present invention, the water-dispersible binder may include or consist of a fluoride-based polymer.
[0021] On the other hand, in one embodiment of the present invention, in the aqueous positive electrode slurry, at least a portion of the fluoride-based polymer particles may be attached to the surface of the positive electrode active material particles.
[0022] A fourth aspect of the present invention provides a positive electrode composition, comprising a positive electrode binder composition and positive electrode active material particles, wherein the positive electrode binder composition comprises a fluoride-based polymer and a water-soluble polymer containing CMC.
[0023] According to a fifth aspect of the present invention, the fluoride-based polymer in the fourth aspect has an average particle diameter of 50 nm to 250 nm.
[0024] According to the sixth aspect of the present invention, the ratio of the water-soluble polymer to the fluoride-based polymer in the fourth or fifth aspect may increase in the direction outward from the surface of the positive electrode active material particle.
[0025] A seventh aspect of the present invention provides a lithium ion secondary battery comprising the positive electrode composition according to any one of the fourth to sixth aspects.
[0026] An eighth aspect of the present invention provides a method for manufacturing an aqueous slurry for a positive electrode, the method comprising the following steps:
[0027] mixing a fluoride-based polymer, a water-soluble polymer, and a positive electrode active material to obtain a mixture; and
[0028] The mixture is dispersed in an aqueous solvent.
[0029] According to a ninth aspect of the present invention, in the method for manufacturing an aqueous slurry for a positive electrode according to the eighth aspect, the step of obtaining a mixture may include:
[0030] mixing the fluoride-based polymer and the positive electrode active material; and
[0031] Add the water soluble polymer and mix.
[0032] A tenth aspect of the present invention provides a method for manufacturing a positive electrode composition, the method comprising the following steps:
[0033] mixing a fluoride-based polymer, a water-soluble polymer including CMC, and a positive electrode active material to obtain a mixture;
[0034] dispersing the mixture in an aqueous solvent to obtain an aqueous slurry for a positive electrode;
[0035] coating the positive electrode with an aqueous slurry on a positive electrode current collector; and
[0036] The aqueous solvent is dried.
[0037] According to an eleventh aspect of the present invention, in the method for manufacturing a positive electrode composition according to the tenth aspect, the step of obtaining a mixture comprises:
[0038] mixing a fluoride-based polymer powder and a positive electrode active material powder; and
[0039] Add water soluble polymer and mix.
[0040] A twelfth aspect of the present invention provides a method for manufacturing a lithium ion secondary battery, the method comprising the method for manufacturing a positive electrode composition according to the tenth or eleventh aspect.
[0041] Beneficial Effects
[0042] The aqueous slurry for a positive electrode, the positive electrode composition and the lithium ion secondary battery according to the present invention can impart lithium ion conductivity, adhesion and chemical stability to the positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The cycle characteristics of Examples 1 and 2 and Comparative Examples 1 to 5 are shown. DETAILED DESCRIPTION
[0044] Hereinafter, the present invention will be described in more detail to help fully understand the present invention.
[0045] In this case, it should be understood that the terms or words used in the specification and the appended claims should not be interpreted as limited to the general and dictionary meanings, but should be interpreted according to the meanings and concepts corresponding to the technical aspects of the present invention on the basis of the principle that the inventor appropriately defines the terms for the best interpretation.
[0046] 〈Aqueous slurry for positive electrode〉
[0047] The present invention relates to an aqueous positive electrode slurry, the aqueous positive electrode slurry comprising a positive electrode active material, a positive electrode binder composition and an aqueous solvent. The positive electrode binder composition comprises a water-dispersible binder and a water-soluble polymer, and the water-dispersible binder may comprise a fluoride polymer or be composed of a fluoride polymer. Preferably, in the aqueous positive electrode slurry, the positive electrode binder composition is composed of a fluoride polymer as a binder. On the other hand, in one embodiment of the present invention, the fluoride polymer includes a PVDF polymer containing vinylidene fluoride (VDF) as a monomer. Specific examples of PVDF polymers may include PVDF homopolymers, poly (vinylidene fluoride-to-hexafluoropropylene) (PVDF-HFP), poly (vinylidene fluoride-to-chlorotrifluoroethylene) (PVDF-CTFE), poly (vinylidene fluoride-to-tetrafluoroethylene) (PVDF-TFE), poly (vinylidene fluoride-to-trifluoroethylene) (PVDF-TrFE). In a specific embodiment of the present invention, the water-dispersible binder may be composed of a fluoride polymer, particularly a PVDF polymer. That is, the water-dispersible binder includes at least one selected from the group consisting of: PVDF homopolymer, PVDF-HFP, PVDF-CTFE, PVDF-TFE, and PVDF-TrFE. For example, the water-dispersible binder may be composed of PVDF. In addition, in the aqueous positive electrode slurry, the positive electrode active material and the water-dispersible binder are dispersed in an aqueous solvent.
[0048] In this specification, a binder refers to a material that imparts adhesion, binding, thickening and coating properties to the components of the positive electrode. In the present invention, the binder may contain a PVDF-based polymer or be composed of a PVDF-based polymer. Preferably, in the aqueous positive electrode slurry of the present invention, the binder may be composed of a PVDF-based polymer.
[0049] On the other hand, the positive electrode binder composition may further include functional additives to improve the adhesion, bonding, thickening and / or coating properties or electrochemical properties of the positive electrode manufactured by the solvent / solution in which the functional additive is dissolved / dispersed or by coating the solvent / solution and drying.
[0050] Preferably, the positive electrode binder composition comprises a PVDF polymer and a water-soluble polymer CMC. More preferably, the positive electrode binder composition according to the present invention is composed of a PVDF polymer and CMC. The positive electrode binder composition comprising a PVDF polymer and CMC can impart lithium ion conductivity, adhesion and chemical stability to the positive electrode.
[0051] 〈Water-soluble polymer〉
[0052] Water-soluble polymer refers to a polymer that is at least partially dissolved when added to an aqueous solvent. Before it is added to an aqueous solvent, the water-soluble polymer can be a variety of phases, such as powder, gel, viscous liquid, block. In one embodiment, the water-soluble polymer can be a powder. In one embodiment of the invention, the water-soluble polymer can include at least one of: carboxymethyl cellulose (CMC), polyacrylate, polyvinyl alcohol, polyacrylamide, polyethylene oxide, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polypropylene, ethylene propylene diene rubber (EPDM), fluororubber or its copolymer. Preferably, the water-soluble polymer can include CMC.
[0053] Preferably, a water-dispersible adhesive may be used as an aqueous adhesive dispersed in an aqueous solvent.
[0054] Because PVDF polymers are almost insoluble or completely insoluble in aqueous solvents unless they are treated separately, PVDF polymers are dispersed in aqueous solvents. For this reason, when PVDF polymer powders are mixed with positive electrode active material particles in an aqueous solvent and dried, the PVDF polymer powders may contact and adhere to the surface of the positive electrode active material particles. In addition, even in the case of dry mixing without using a solvent, PVDF polymer powders may contact and adhere to the surface of the positive electrode active material particles after mixing. The contact may be point contact.
[0055] Before the PVDF-based polymer is dispersed in the aqueous solvent, the PVDF-based polymer is not limited to a specific phase and may be in the form of a block, powder, paste, and liquid. In the specification, unless the context clearly indicates otherwise, the PVDF-based polymer is a powder.
[0056] PVDF-based polymers can act as a binder to promote the bonding between surrounding components containing PVDF-based polymers, and act as a conductive path for lithium ions when swollen after being wetted by the electrolyte. When PVDF-based polymers are attached to the surface of positive electrode active material particles and swell after being wetted by the electrolyte, PVDF-based polymers can promote the conduction of lithium ions between the positive electrode active material particles and the electrolyte.
[0057] Relative to 100 parts by weight of the positive electrode composition, the content of the PVDF-type polymer may be 0.1 parts by weight to 10 parts by weight. Relative to 100 parts by weight of the positive electrode composition, the content of the PVDF-type polymer may be 0.5 parts by weight to 5 parts by weight. Preferably, the content of the PVDF-type polymer may be 1 parts by weight to 3 parts by weight relative to 100 parts by weight of the positive electrode composition. When the content of the PVDF-type polymer is within the above range, the PVDF-type polymer may impart lithium ion conductivity to the positive electrode. When the amount of the PVDF-type polymer is greater than the above range, the amount of positive electrode active material in the positive electrode composition is reduced, and the positive electrode capacity is reduced. When the amount of the PVDF-type polymer is less than the above range, the conduction path of lithium ions between the positive electrode active material particles and the electrolyte is reduced, and the cycle characteristics are deteriorated.
[0058] As described above, unless processed separately, PVDF polymers can be dispersed in aqueous solvents. In one embodiment, a premix of PVDF polymer powder and positive active material particles can be used. Considering the size of PVDF polymer and positive active material particles or the size of positive active material particles, any other binder and conductive material dispersed in PVDF polymer and positive electrode aqueous slurry, the average particle size of PVDF polymer can be in the submicron level. For example, the average particle size of PVDF polymer can be in the range of 50nm to 250nm. In addition, the average particle size of PVDF polymer can be in the range of 100nm to 200nm. When the average particle size of PVDF polymer is within the above range, positive active material particles and PVDF polymer powder can be well mixed, and as a result, PVDF polymer can be attached to the surface of positive active material particles. Therefore, the PVDF polymer between positive active material particles and electrolyte promotes the conduction of lithium ions during charge / discharge of lithium ion secondary battery. When the average particle size of the PVDF polymer is higher than the above range, the PVDF polymer may not be uniformly mixed with the positive electrode active material particles, and as a result, the positive electrode composition may have an uneven composition, and the cycle characteristics of the lithium ion secondary battery manufactured using the composition may deteriorate. When the average particle size of the PVDF polymer is less than the above range, the PVDF polymer powder may aggregate. Therefore, the mixing of the PVDF polymer and the positive electrode active material particles may be uneven, and as a result, the positive electrode composition may have an uneven composition, and the cycle characteristics of the lithium ion secondary battery manufactured using the composition may deteriorate. The average particle size of the PVDF polymer can be measured by common methods such as laser diffraction, optical and electron microscopy, and sieving analysis.
[0059] Unless treated separately, CMC dissolves in aqueous solvents and can impart thickening properties to aqueous solvents. Therefore, when CMC powder is dissolved in an aqueous solvent, mixed with positive active material particles and dried, at least a portion of the surface of the positive active material particles can be coated with CMC.
[0060] Before it is dissolved in an aqueous solvent, CMC is not limited to a specific phase and may be in the form of a block, powder, paste, and liquid. In the specification, unless the context clearly indicates otherwise, CMC is a powder before it is dissolved in an aqueous solvent.
[0061] CMC acts as a binder or thickener when mixed with positive electrode active material particles to improve adhesion in the positive electrode composition and the positive electrode.
[0062] The CMC coated on the positive electrode active material particles separates the electrolyte from the positive electrode active material to suppress a side reaction between the electrolyte and the positive electrode active material.
[0063] In one embodiment of the present invention, the content of CMC may be 0.1 to 10 parts by weight relative to 100 parts by weight of the positive electrode composition. The content of CMC may be 0.5 to 5 parts by weight relative to 100 parts by weight of the positive electrode composition. Preferably, the content of CMC may be 0.5 to 2.5 parts by weight relative to 100 parts by weight of the positive electrode composition. More preferably, the content of CMC may be 0.8 to 2.5 parts by weight relative to 100 parts by weight of the positive electrode composition. When the content of CMC is within the above range, CMC may impart adhesion and chemical stability to the positive electrode. When the amount of CMC is higher than the above range, the amount of positive active material in the positive electrode composition is reduced and the positive electrode capacity may be reduced.
[0064] Here, adhesion refers to the adhesion performance between the elements of the positive electrode, and high adhesion prevents the peeling of the active material composition from the current collector or the separation of the active material from the active material composition during charge / discharge. In addition, it is expected that the side reaction between the positive electrode active material particles and the electrolyte is prevented due to the coating performance of CMC, and when the amount of CMC is greater than the above range, a thick CMC coating is formed on the surface of the positive electrode active material particles, and the lithium ion conductivity between the positive electrode active material particles and the electrolyte may be reduced. When the amount of CMC is less than the above range, the adhesion in the positive electrode composition is reduced and the cycle characteristics may be deteriorated, and when an aqueous solvent is used to mix with the positive electrode active material particles, the positive electrode active material particles are not fully coated, and the side reaction between the positive electrode active material particles and the electrolyte cannot be prevented.
[0065] The present invention combines PVDF, which promotes lithium ion conduction between positive electrode active material particles and electrolyte, with CMC, which increases the adhesion of the positive electrode and prevents side reactions between the positive electrode active material particles and electrolyte, thereby achieving high lithium ion conductivity and stable adhesion, and preventing side reactions of the positive electrode.
[0066] The weight ratio of the PVDF-based polymer to the CMC may be 1:9 to 9:1, preferably 1: 1. When the weight ratio is within the above range, lithium ion conductivity, adhesion, and chemical stability may be imparted to the positive electrode.
[0067] The ratio of CMC to PVDF-based polymers can increase or decrease in the direction from the surface of the positive electrode active material particles to the outside. In one embodiment, the ratio of CMC to PVDF increases in the direction from the surface of the positive electrode active material particles to the outside. In this case, near the surface of the positive electrode active material particles, PVDF exists in large quantities and CMC exists in small quantities. When PVDF exists in large quantities near the surface of the positive electrode active material, PVDF swells after being wetted by the electrolyte, thereby easily establishing a conductive path for lithium ions.
[0068] 〈Aqueous solvent〉
[0069] The solvent uses an aqueous solvent instead of an organic solvent such as N-methyl-2-pyrrolidone (NMP) which is generally used to dissolve the binder. In one embodiment of the present invention, the aqueous solvent can disperse the water-insoluble PVDF-based polymer and dissolve the water-soluble CMC.
[0070] The aqueous solvent may be a polar protic solvent. The polar protic solvent may include water, alcohol, acetate, formates or a combination thereof.
[0071] The aqueous solvent may be a solvent containing water as a main component. The aqueous solvent may contain a polar protic solvent other than water. The amount of the polar protic solvent other than water contained in the aqueous solvent may be less than 10 parts by weight, preferably less than 5 parts by weight, more preferably less than 1 part by weight, relative to 100 parts by weight of the aqueous solvent.
[0072] Preferably, the aqueous solvent may be water. When the aqueous solvent is water, PVDF may be dispersed in water, and when the dispersion is dried, PVDF may adhere to the surface of the positive electrode active material particles. Therefore, PVDF may be used to establish a lithium ion conduction path between the positive electrode active material particles and the electrolyte during charge / discharge.
[0073] The aqueous solvent is used in an amount large enough to dissolve or disperse the positive electrode active material, the conductive material and the binder in consideration of the coating thickness or yield of the slurry, and has a sufficiently high viscosity to ensure high thickness uniformity when coating is performed to manufacture a positive electrode.
[0074] 〈Lithium-ion secondary battery〉
[0075] The present invention provides a lithium ion secondary battery, which comprises a positive electrode composition prepared using the slurry of the present invention. The lithium ion secondary battery comprises a positive electrode, a negative electrode opposite to the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte.
[0076] Optionally, the lithium ion secondary battery may further include a battery container receiving the electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member sealing the battery container.
[0077] There is no particular limitation on the shape of the lithium ion secondary battery of the present invention, but the lithium ion secondary battery may have a cylindrical shape, a prismatic shape, a pouch shape, or a coin shape using a can.
[0078] <positive electrode>
[0079] The positive electrode includes a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector, and the positive electrode active material layer includes a positive electrode composition.
[0080] The positive electrode collector includes any type of positive electrode collector having conductivity without causing chemical changes to the battery, such as: stainless steel, aluminum, nickel, titanium, sintered carbon; or aluminum or stainless steel treated with carbon, nickel, titanium and silver on the surface. In addition, generally, the thickness of the positive electrode collector is 3 μm to 500 μm, and in order to improve the adhesion of the positive electrode active material, the collector may have fine concavoconvexities on the surface. For example, the positive electrode collector may have various shapes, such as films, sheets, foils, nets, porous bodies, foams and non-woven fabrics.
[0081] <Positive Electrode Composition>
[0082] The positive electrode composition may further include a conductive material and a binder in addition to the positive electrode active material.
[0083] 〈Positive electrode active material〉
[0084] The positive electrode active material includes any type of material capable of intercalating and deintercalating lithium ions, but currently, in order to realize a battery having excellent life characteristics and charge / discharge efficiency, lithium transition metal oxides are generally used as positive electrode active materials.
[0085] Lithium transition metal oxides may contain transition metals, for example: layered compounds substituted by at least one transition metal such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2); lithium manganese oxide substituted by at least one transition metal; lithium nickel oxide; spinel lithium nickel manganese composite oxides; spinel lithium manganese oxides in which Li is partially replaced by alkaline earth metal ions; olivine lithium metal phosphates, but are not limited to these.
[0086] Preferably, a lithium-containing transition metal oxide is used, such as at least one selected from the following: LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li2NiO2, Li(Ni a Co b Mn c )O2 (0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), LiNi 1-Y Co Y O2, LiCo 1-Y Mn Y O2, LiNi 1-Y Mn Y O2 (0 ≤ Y < 1), Li(Ni a Co b Mn c )O4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-z Ni z O4, LiMn 2-z Co z O4 (0 < Z < 2), Li x M y Mn 2-y O 4-z A z (0.9 ≤ x ≤ 1.2, 0 < y < 2, 0 ≤ z < 0.2, M is at least one of Al, Mg, Ni, Co, Fe, Cr, V, Ti, Cu, B, Ca, Zn, Zr, Nb, Mo, Sr, Sb, W, Ti or Bi, and A is at least one of a monovalent (-1) anion or a divalent (-2) anion), Li 1+a Ni b M' 1-b O 2-c A' c (0 ≤ a ≤ 0.1, 0 ≤ b ≤ 0.8, 0 ≤ c < 0.2, M' is at least one selected from stable 6 - coordinate elements such as Mn, Co, Mg, Al, and A' is at least one of a monovalent (-1) anion or a divalent (-2) anion), LiCoPO4 and LiFePO4, and preferably LiCoO2. In addition to these oxides, sulfides, selenides, and halides can also be used.
[0087] Preferably, LiCoO2 is used as the positive electrode active material.
[0088] With respect to 100 parts by weight of the positive electrode composition, the content of the positive electrode active material can be 80 to 99 parts by weight, more specifically 85 to 98.5 parts by weight. When the content of the positive electrode active material is within the above range, excellent capacity characteristics can be provided.
[0089] The average particle size of the positive electrode active material particles is 1 μm to 50 μm, preferably 5 μm to 30 μm. When the average particle size of the positive electrode active material particles is within the above range, the capacity characteristics of the battery are excellent. The average particle size of the positive electrode active material particles can be measured by a known method such as an electron microscope.
[0090] The average particle size of the positive electrode active material particles may be larger than that of the binder. When the average particle size of the positive electrode active material particles is larger than that of the binder, the binder may adhere to the surface of the positive electrode active material during mixing.
[0091] 〈Conductive Materials〉
[0092] The conductive material is used to impart conductivity to the electrode, and includes any type of conductive material having conductivity in the battery. Specific examples may include at least one of the following: graphite such as natural graphite or artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber; metal powder or metal fiber of copper, nickel, aluminum, silver; conductive whiskers of zinc oxide, potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives. The content of the conductive material may be 0.1 parts by weight to 15 parts by weight relative to 100 parts by weight of the positive electrode composition.
[0093] For example, the positive electrode active material layer may be formed by coating a positive electrode active material layer-forming composition prepared by dissolving or dispersing a positive electrode active material and optionally a binder and a conductive material in a solvent on a positive electrode current collector and drying; or
[0094] It can be manufactured by casting the positive electrode active material layer forming composition on a support, and laminating the film separated from the support on a positive electrode current collector.
[0095] <negative electrode>
[0096] In a lithium ion secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.
[0097] The negative electrode current collector includes any type of negative electrode current collector having high conductivity without causing chemical changes to the battery, such as: copper, stainless steel, aluminum, nickel, titanium, sintered carbon; copper or stainless steel treated with carbon, nickel, titanium and silver on the surface; aluminum-cadmium alloy. In addition, generally, the thickness of the negative electrode current collector is 3 μm to 500 μm, and in the same manner as the positive electrode current collector, in order to improve the binding of the negative electrode active material, the current collector may have fine concavoconvexities on the surface. For example, the negative electrode current collector may have various shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0098] The negative electrode active material layer optionally contains a binder and a conductive material in addition to the negative electrode active material.
[0099] The negative electrode active material may include a compound that can reversibly intercalate and deintercalate lithium. Specific examples may include at least one of the following: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon; (semi)metallic materials that can form alloys with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy or Al alloy; (semi)metallic oxides that can be doped and undoped with lithium such as SiO β (0<β<2), SnO2, vanadium oxide, lithium vanadium oxide; or a composite material comprising a (semi) metal material and a carbonaceous material such as a Si-C composite material or a Sn-C composite material. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, the carbon material can include low-crystalline carbon and high-crystalline carbon. Low-crystalline carbon generally includes soft carbon and hard carbon, and high-crystalline carbon generally includes amorphous, plate-like, flaky, spherical or fibrous high-temperature sintered carbon such as natural graphite or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesophase carbon microbeads, mesophase pitch, and coal and petroleum coke.
[0100] The content of the negative electrode active material may be 80 parts by weight to 99 parts by weight relative to 100 parts by weight of the negative electrode active material layer.
[0101] The binder for the negative electrode is used to assist the bonding between the conductive material, the active material and the current collector, and the amount of the binder added is 0.1 to 10 parts by weight relative to 100 parts by weight of the negative electrode active material layer. Examples of the binder may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber and copolymers thereof.
[0102] The conductive material is used to further improve the conductivity of the negative electrode active material, and the amount of the conductive material added can be 10 parts by weight or less, preferably 5 parts by weight or less relative to 100 parts by weight of the negative electrode active material layer. The conductive material is not limited to a specific type, and preferably includes any type of conductive material that has conductivity and, in particular, does not cause chemical changes to the corresponding battery. For example, the conductive material may include: graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; carbon fluoride; metal powders such as aluminum and nickel powders; conductive whiskers of zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives.
[0103] For example, the negative electrode active material layer can be formed by coating a composition for forming the negative electrode active material layer prepared by dissolving or dispersing the negative electrode active material and optional binder and conductive material in a solvent on a negative electrode collector and drying; or can be manufactured by casting the composition for forming the negative electrode active material layer on a carrier and laminating the film separated from the carrier on the negative electrode collector.
[0104] 〈Diaphragm〉
[0105] The separator separates the negative electrode and the positive electrode to provide a mobile channel for lithium ions, and may include any type of separator commonly used in lithium ion secondary batteries, in particular, the separator preferably has low resistance to the movement of electrolyte ions and high electrolyte wettability. Specifically, for example, the separator may include: a porous polymer film prepared from polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers; or a stacked structure of two or more layers thereof. In addition, commonly used porous non-woven fabrics may include, for example, non-woven fabrics made of high melting point glass fibers and polyethylene terephthalate fibers. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing ceramic or polymer materials may be used, and may be selectively used in a single-layer or multi-layer structure.
[0106] 〈Electrolyte〉
[0107] The electrolyte may include an organic electrolyte and an inorganic electrolyte that can be used to manufacture a lithium ion secondary battery, but is not limited thereto.
[0108] The electrolyte may include an organic solvent and a lithium salt.
[0109] The organic solvent may include any type of organic solvent used as a medium that allows the movement of ions participating in the electrochemical reaction of the battery. Specifically, the organic solvent may include: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (R is a straight chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms and may contain a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. Among these solvents, carbonate solvents are desirable, and a mixture of cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) with a low viscosity chain carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) having high ionic conductivity and high dielectric constant to improve the charge / discharge performance of the battery is more desirable. In this case, a mixture having a volume ratio of about 1:1 to about 1:9 of cyclic carbonate and chain carbonate provides excellent electrolyte performance.
[0110] The lithium salt may include any type of compound capable of providing the lithium ions used in the lithium ion secondary battery. Specifically, the lithium salt may include LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2. The concentration of the lithium salt used may be in the range of 0.1M to 2.0M. When the concentration of the lithium salt is included in the above range, the electrolyte has appropriate conductivity and viscosity, and shows excellent electrolyte performance, thereby achieving efficient movement of lithium ions.
[0111] In order to improve the life characteristics of the battery, prevent the reduction of the battery capacity and increase the discharge capacity of the battery, in addition to the electrolyte components, the electrolyte may also contain at least one additive, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum chloride. In this case, the content of the additive may be 0.1 to 5 parts by weight relative to 100 parts by weight of the electrolyte.
[0112] Hereinafter, embodiments of the present invention will be described in sufficient detail to enable those skilled in the art to easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the embodiments described herein.
[0113] [Manufacturing of coin batteries]
[0114] In the examples and comparative examples of the present invention, PVDF polymer was used as the fluoride-based polymer.
[0115] (Example 1)
[0116] 96 parts by weight of LiCoO2 as a positive electrode active material and 1 part by weight of PVDF powder were mixed using a mixer (Thinky, ARE-310) so that PVDF was loaded on the surface of the LiCoO2 particles. 2 parts by weight of conductive carbon black (Super P TM ) and 1 part by weight of CMC as a water-soluble polymer for imparting thickening properties to the aqueous slurry for the positive electrode. Subsequently, pure water is added to have a viscosity for obtaining good thickness uniformity in the coating process for manufacturing the positive electrode, thereby obtaining an aqueous slurry for the positive electrode. The obtained aqueous slurry for the positive electrode is coated on a 20 μm thick aluminum foil to a thickness of about 60 μm, and vacuum dried overnight at 120°C to manufacture a positive electrode sheet in which the positive electrode composition is deposited on the aluminum foil. The obtained positive electrode sheet is punched into a circular shape, which is a circle with a diameter of 13 mm and an electrode density of 3.8 g / cc to 3.9 g / cc, thereby manufacturing a positive electrode. A 2016 coin cell is manufactured using the obtained positive electrode, 0.3 mm thick metallic lithium as a counter electrode, and an electrolyte containing EC:DMC:DEC and 1MLiPF6 in a volume ratio of 1:2:1.
[0117] (Example 2)
[0118] 96 parts by weight of LiCoO2 as a positive electrode active material, 1 part by weight of PVDF powder as a binder composition, 1 part by weight of CMC as a water-soluble polymer for imparting thickening properties to the positive electrode aqueous slurry, and 2 parts by weight of Super P as a conductive material were mixed together so that PVDF and CMC were loaded on the surface of the LiCoO2 particles. Pure water was added thereto to obtain an aqueous slurry for the positive electrode. Subsequently, a coin cell was manufactured using the same method as in Example 1.
[0119] (Comparative Example 1)
[0120] A coin cell was manufactured by the same method as in Example 2 except that an organic solvent NMP was used instead of pure water as the aqueous solvent, and 2 parts by weight of PVDF was used instead of 1 part by weight of PVDF and 1 part by weight of CMC.
[0121] (Comparative Example 2)
[0122] A coin cell was manufactured by the same method as in Example 2, except that 1 part by weight of CMC was used instead of 1 part by weight of PVDF and 1 part by weight of CMC.
[0123] (Comparative Example 3)
[0124] A coin cell was manufactured by the same method as in Example 2, except that 2 parts by weight of CMC was used instead of 1 part by weight of PVDF and 1 part by weight of CMC.
[0125] (Comparative Example 4)
[0126] A coin cell was manufactured by the same method as in Example 2, except that 1 part by weight of SBR and 1 part by weight of CMC were used instead of 1 part by weight of PVDF and 1 part by weight of CMC.
[0127] (Comparative Example 5)
[0128] A coin cell was manufactured by the same method as in Example 2, except that 1 part by weight of PVDF, 0.5 part by weight of SBR, and 0.5 part by weight of CMC were used instead of 1 part by weight of PVDF and 1 part by weight of CMC.
[0129] The differences in the composition of the positive electrode compositions and the binder mixing order in Examples 1 and 2 and Comparative Examples 1 to 3 are shown in the following Table 1. Each value in Table 1 shows parts by weight relative to 100 parts by weight of the positive electrode composition including a positive electrode active material, PVDF, a water-soluble polymer and a conductive material.
[0130] [Table 1]
[0131] Composition of positive electrode composition and mixing order of binder
[0132]
[0133] [1] Evaluation of positive electrode peeling test
[0134] The peel strength of the positive electrode of the coin cells obtained in Examples 1 and 2 and Comparative Examples 1 to 3 was measured using a measuring device (SHIMADZU, EZ-SX) under a peeling speed of 300 mm / min. The sample was obtained in the following manner: a double-sided tape of 15 mm in width and 60 mm in length was attached to one surface of a slide glass, and a sample obtained by cutting the positive electrode into a size of 15 mm in width and 150 mm in length was attached to the opposite surface. The results are shown in Table 2 below.
[0135] [Table 2]
[0136] Peel strength
[0137]
[0138] Under the condition of no pressing, Example 1 showed the highest average test value of 0.245 [N]. The peel strength of Comparative Example 2 showed 0.68 [N] as the initial peak value, but the average test value was very close to zero, and it was less than the average test value of 0.083 [N] of Comparative Example 3. On the other hand, Figure 1 As shown, among Comparative Examples 2 and 3, Comparative Example 3 shows worse cycle characteristics. Therefore, in the case of a positive electrode active material having a small volume change during charge / discharge, it is considered that the binding property and adhesion property of the binder have little influence on the cycle characteristics.
[0139] [2] Evaluation of cycle characteristics and capacity retention
[0140] In order to determine whether lithium ion conductivity, adhesion and chemical stability are imparted to the positive electrode, the cycle characteristics and capacity retention rates of the coin cells manufactured in Examples 1 and 2 and Comparative Examples 1 to 5 were evaluated as follows. It is presumed that when the lithium ion conductivity is high, the transport of lithium ions during charge / discharge is smooth, when the adhesion is good, the bonding between the components of the positive electrode is improved, and when the chemical stability is high, the deterioration of the binder and the active material is prevented, thereby improving the cycle characteristics and capacity retention rate.
[0141] The cycle characteristics were evaluated by charging / discharging various coin cells at 25° C. and 45° C. Specifically, after charging / discharging various coin cells in a voltage range of 4.55 V to 3 V at a current rate of 0.2 C charge and 0.2 C discharge in a thermostat maintained at 25° C. for several cycles, each coin cell was moved to a thermostat maintained at 45° C., and then charging / discharging was repeated for 50 cycles at a current rate of 0.5 C charge and 1 C discharge in a voltage range of 4.55 V to 3 V.
[0142] The values of the initial charge capacity measured at each temperature for each Example and Comparative Example when the initial capacity of Comparative Example 1 at each temperature is 100 are shown in the following Table 3. On the other hand, the initial cycle at 45° C. is the 6th cycle of the battery.
[0143] [Table 3]
[0144] Initial capacity based on Comparative Example 1
[0145] Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 25℃ 100 99 100 98 97 93 94 45℃ 100 99 100 98 97 94 94
[0146] Regardless of the measurement temperature, Example 1 using an aqueous positive electrode slurry obtained an initial capacity equivalent to that of Comparative Example 1 using an NMP solvent. Example 2, in which the binder mixing order is different from that of Example 1, obtained an initial capacity of 99, which is lower than the initial capacity of Comparative Example 1. Comparative Examples 2 and 4 using only CMC as a binder obtained initial capacities of 98 and 97, respectively. Comparative Examples 4 and 5 containing SBR in the electrode composition obtained initial capacities of 93 and 94, respectively. Compared with Comparative Examples 2 and 3 not containing PVDF as a binder, Examples 1 and 2 and Comparative Example 1 containing PVDF as a binder obtained higher initial capacities. It is speculated that PVDF swells after being wetted by the electrolyte and acts as a conduction path for lithium ions, thereby promoting the conduction of lithium ions between the positive electrode active material particles and the electrolyte. In addition, it is believed that the significant reduction in the initial capacity of Comparative Examples 4 and 5 containing SBR in the electrode composition is caused by the well-known decomposition of SBR on the oxidized surface.
[0147] Then, the results of the cycle characteristics are shown in Figure 1 Reference Figure 1 , in Example 1 where the positive electrode active material and PVDF were mixed and then CMC was added, the cycle characteristics were the best. In Example 2 where the positive electrode active material, PVDF, and CMC were mixed simultaneously, the cycle characteristics were the same as those of Comparative Example 1 using NMP as an organic solvent. Comparative Examples 2 and 3 using only CMC as a binder had worse cycle characteristics than Example 1, and Comparative Examples 4 and 5 containing SBR in the electrode composition showed the lowest cycle characteristics and showed significant deterioration during the cycle such as abnormal changes in the retention rate.
[0148] In addition, Table 4 shows the ratio of the binder contained in the positive electrode composition and the capacity retention ratio indicated as the ratio of the capacity after the 50th cycle / the capacity after the 1st cycle.
[0149] [Table 4]
[0150] Capacity retention rate
[0151]
[0152] Referring to Table 4, Example 2 exhibits a capacity retention rate of 81.5%, which is equal to the capacity retention rate of 81.5% of Comparative Example 1. When an aqueous solvent is used as a dispersion medium for the positive electrode slurry, the same cycle characteristics and capacity retention rate as those when an organic solvent is used in the past can be achieved. It is speculated that the combination of PVDF and CMC as an aqueous binder can give the positive electrode improved lithium ion conductivity, adhesion and chemical stability, thereby improving the cycle characteristics and capacity retention rate.
[0153] In addition, Example 1 exhibited the highest capacity retention rate of 89.1%. In Example 1, since the positive electrode active material and PVDF were mixed and then CMC was added, it is presumed that PVDF was first attached to the surface of the positive electrode active material and then CMC was coated on the positive electrode active material. Therefore, it is presumed that, compared with Example 2 in which the positive electrode active material, PVDF, and CMC were mixed simultaneously, as the ratio of PVDF to CMC on the surface of the positive electrode active material particles increased, the lithium ion conduction path between the positive electrode active material and the electrolyte increased, thereby improving the cycle characteristics and capacity retention rate.
[0154] Comparative Examples 2 and 3 showed a capacity retention rate of less than 80%. Since the positive electrode active material was mostly coated with CMC, the adhesion and chemical stability were improved, but it is presumed that the conduction path of lithium ions was reduced by the coating, and as a result, the cycle characteristics were reduced and the capacity retention rate was reduced.
[0155] Comparative Examples 4 and 5 showed a capacity retention rate of less than 70%. In the same manner as Comparative Examples 2 and 3, it is presumed that the conduction path of lithium ions is reduced due to the coating of CMC and the capacity retention rate is reduced due to the oxidative decomposition of SBR.
[0156] In addition, although not shown, when the voltage is 4.50V lower than 4.55V or the temperature is 25°C lower than 45°C, Examples 1 and 2 and Comparative Example 1 show the same cycle characteristics and capacity retention rate. It can be seen that the positive electrode of Example 1 has high lithium ion conductivity, adhesion and chemical stability under the harsh conditions of a high temperature of 45°C and a high voltage of 4.55V.
Claims
1. An aqueous positive electrode slurry, comprising a positive electrode active material, a water-dispersible binder, a water-soluble polymer and an aqueous solvent, wherein the water-dispersible binder is composed of a fluorinated polymer, The water-soluble polymer comprises carboxymethyl cellulose (CMC), and The positive electrode active material and the water-dispersible binder are dispersed in the aqueous positive electrode slurry, The aqueous positive electrode slurry is prepared by the following method, which comprises the following steps: mixing the fluoride-based polymer and the positive electrode active material; adding the water-soluble polymer and mixing to obtain a mixture; and dispersing the mixture in the aqueous solvent, The fluoride-based polymer is in particle form and is at least one selected from the group consisting of polyvinylidene fluoride (PVDF), PVDF-HFP, PVDF-CTFE, PVDF-TrFE, and PVDF-TFE. 2 . The aqueous cathode slurry according to claim 1 , wherein the fluoride-based polymer has an average particle size of 50 nm to 250 nm. The aqueous cathode slurry according to claim 1 , wherein the aqueous solvent is water.
4. A positive electrode composition, comprising: A positive electrode binder composition, comprising: a fluoride-based polymer; and a water-soluble polymer containing carboxymethyl cellulose (CMC); and Positive electrode active material particles, wherein the ratio of the water-soluble polymer to the fluoride-based polymer increases in a direction outward from the surface of the positive electrode active material particle, The positive electrode composition is prepared by using the aqueous positive electrode slurry according to claim 1. The cathode composition according to claim 4 , wherein the fluoride-based polymer has an average particle diameter of 50 nm to 250 nm.
6. The cathode composition according to claim 4, wherein the cathode active material consists of lithium cobalt oxide (LiCoO2). 7 . A lithium ion secondary battery comprising the positive electrode composition according to claim 4 .
8. A method for manufacturing an aqueous slurry for a positive electrode, the method comprising the following steps: mixing a fluoride-based polymer, a water-soluble polymer including carboxymethyl cellulose (CMC), and a positive electrode active material to obtain a mixture; and dispersing the mixture in an aqueous solvent, The step of obtaining the mixture comprises: mixing the fluoride-based polymer and the positive electrode active material; as well as Add the water-soluble polymer and mix, The fluoride-based polymer is in particle form and is at least one selected from the group consisting of polyvinylidene fluoride (PVDF), PVDF-HFP, PVDF-CTFE, PVDF-TrFE, and PVDF-TFE.
9. A method for manufacturing a positive electrode composition, the method comprising the following steps: mixing a fluoride-based polymer, a water-soluble polymer including carboxymethyl cellulose (CMC), and a positive electrode active material to obtain a mixture; dispersing the mixture in an aqueous solvent to obtain an aqueous slurry for a positive electrode; coating the positive electrode with an aqueous slurry on a positive electrode current collector; as well as drying the aqueous solvent, The step of obtaining the mixture comprises: mixing the fluoride-based polymer and the positive electrode active material; as well as Add the water-soluble polymer and mix, The fluoride-based polymer is in particle form and is at least one selected from the group consisting of polyvinylidene fluoride (PVDF), PVDF-HFP, PVDF-CTFE, PVDF-TrFE, and PVDF-TFE. 10 . A method for manufacturing a lithium ion secondary battery, the method comprising the method for manufacturing a positive electrode composition according to claim 9 .
Citation Information
Patent Citations
Manufacturing method of electrode plate for negative electrode of nonaqueous secondary battery
JP2006107896A
Aqueous binder liquid for secondary battery positive electrode, aqueous paste for secondary battery positive electrode produced with aqueous binder liquid, secondary battery positive electrode, and secondary battery
JP2014063676A
Aqueous binder composition for positive electrode and aqueous positive electrode composition
JP2015088276A
Nonaqueous electrolyte secondary battery
JP1992155776A
Nonaqueous electrolyte secondary battery and manufacture of positive plate of the nonaqueous electrolyte secondary battery
JP2000106186A